Crime analysis of San Carlos City, Pangasinan - Bautista, Jorwin Dela Cruz (Panpacific University : [s.n.], 2018)
This study aimed to map and analyze reported criminal incidents in the City of San Carlos, Pangasinan for the period of 2015 and 2016.
Bibliography: pages 100-102.
CHED-La Union
Keywords: Crime analysis